Integrated Logistic Centers : Experience from North America and Options for China - Blancas, Luis C. (World Bank, Washington, DC, 2015)
China s shift toward accelerated economic growth in central and western provinces and increasing levels of personal income and consumption are all consistent with the need for rail-enabled Integrated Logistics Centers (ILCs). Yet, while hundreds of logistics clusters have been developed in China over the past few years, modern, international standard rail- and multimodal-transport enabled ILCs are less common. Close, long-term collaboration between public sector authorities and private sector specialized firms, such as real estate developers, have proven effective in the development of North America s focused network of ILCs critical to facilitating transcontinental and other freight itineraries. This model can succeed in China as well. The ready availability of multimodal transport connectivity is the most critical component of any cluster of logistics activities. This note will argue that China could substantially benefit from developing a focused network of well-planned, economically justified, financially viable, and carefully implemented ILCs supported by rail intermodal operations.